Spectroscopic Study on YAG (532) Laser Dyes using DELIF for Oil Film Thickness and Temperature Measurement - Hidrovo, Carlos H.; Hart, Douglas P.; Saeki, Souichi (Journal of the Visualization Society of Japan, 2001)
This paper presents much information about YAG (532) laser dyes dissolved into oil which can be utilized to measure oil film thickness and temperature. A spectroscopy analysis was conducted to obtain fluorescence and absorptivity spectra using spectrofluorometer and spectrophotometer, respectively. Spectroscopic dependency of each single-dye on temperature was evaluated to discover the best indicator of temperature. Some promising combinations of two dyes were selected to be applied to Dual Emission LIF (DELIF) temperature measurement on the basis of this information. The possibility of DELIF were examined using a spectrofluorometer. Consequently, some of the best dye-combinations was recommended, which could make the most of DELIF and Emission Reabsorption LIF (ERLIF) film thickness measurement. The ratio-metric LIF technique was found to be very helpful for minimizing of photo-degradation errors originating from the dye-bleaching and oil-oxidation caused by high temperature.